Motivasi Masyarakat Dalam Aktivitas Olahraga Rekreasi Pada Event Car Free Day Di Karesidenan Pati Tahun 2020 - Abdullah Rizallul Zain; Maftukhin Hudah; Muh Isna Nurdin Wibisana (YLPK Mahardhika, 2020)
This research is based on the fact that there are still visitors who have not been able to fully take advantage of Car Free Day activities to do recreational sports properly. The purpose of this study is to determine the level of community motivation to take part in the Car Free Day Event at the Pati Residency in 2020. The research method used is descriptive quantitative research with survey methods, and collection of information or data using a questionnaire. The population in this study were all people who came to the car free day event in Karesidenan Pati. The sample in this study were 100 respondents who came to the car free day event in Pati Residency from the age of 13-50 years. The sampling technique in this study used purposive sampling. The results showed that of the 100 respondents who had attended the car free day event at the Pati Residency in 2020, they had high motivation of 97.98%. The conclusion of this study is that the level of community motivation in recreational sports activities at the car free day event in the Pati Residency in 2020 is in the high category of 97.98%. Suggestion is that the government is even more active in spatial planning and controlling tires at the car free day location so that visitors feel comfortable. The tourism office should pay more attention to the inadequate facilities and infrastructure in the car free day location to make it even better. For students, they should be able to increase research on recreational sports. Keywords: Residency, Motivation, Recreational Sports, Car Free Day. Abstrak Penelitian ini dilatar belakangi yaitu masih adanya pengunjung yang belum sepenuhnya bisa memanfaatkan aktivitas Car Free Day untuk melakukan olahraga rekreasi dengan baik. Tujuan penelitian ini yaitu untuk mengetahui bagaimana tingkat motivasi masyarakat untuk mengikuti Event Car Free Day di Karesidenan Pati Tahun 2020. Metode penelitian yang digunakan yaitu penelitian deskriptif kuantitatif dengan metode survei, dan pengumpulan informasi atau data menggunakan kuesioner. Populasi dalam penelitian ini adalah seluruh masyarakat yang datang pada event car free day di Karesidenan Pati. Sampel dalam penelitian ini adalah masyarakat yang datang pada event car free day di Karesidenan Pati dari usia 13-50 tahun sebanyak 100 orang responden. Teknik sampling pada penelitian ini menggunakan purposive sampling.Hasil penelitian menunjukkan bahwa dari 100 orang responden yang telah datang di acara car free day di Karesidenan Pati Tahun 2020 memiliki motivasi yang tinggi sebesar 97,98%. Simpulan penelitian ini adalah tingkat motivasi masyarakat dalam aktivitas olahraga rekreasi pada event car free day di Karesidenan Pati Tahun 2020 tergolong dalam kategori tinggi sebesar 97,98%. Saran, pemerintah lebih giat lagi dalam melakukan penataan ruang dan penerti ban di lokasi car free day agar para pengunjung merasa nyaman. Dinas pariwisata agar lebih memperhatikan lagi sarana dan prasarana yang kurang memadai yang ada didalam lokasi car free day agar lebih baik lagi. Untuk mahasiswa, hendaknya bisa memperbanyak penelitian mengenai olahraga rekreasi. Kata Kunci : Karesidenan, Motivasi, Olahraga Rekreasi, Car Free Day.